EFFECT OF COMPENSATION, EMPOWERMENT AND CULTURAL ORGANIZATION TO THE SATISFACTION OF EMPLOYEES PART PRODUCTION IN CV. AKAR SAMUDRA SEMARANG - Maria Magdalena Minarsih (Jurnal Ekonomi dan Bisnis Kontemporer, 2015)
CV Akar Samudra since 2 years has a problem where lower work satisfaction. Low jobsatisfaction experienced by employees allegedly motivated by the low compensation givenby the company, lack of empowerment and the low level of positive organizational culturethat developed in the company.Population in this research is the production employees CV. Ocean root numbering 80people . The number of samples taken in this study is determined through census method.Techniques using multiple linear regression analysis and test hipotesi t and F. Based on theanalysis it can be seen that the variable compensation , empowerment and organizationalculture partial and simultaneous effect on employee satisfaction can be accepted.Keywords: compensation, leadership styles, organizational culture and job satisfaction